Español - Español; Español; Español (Ars Pharmaceutica (Internet), 1980)
Lead has been determinated in sorne samples of diferents canned goods of fishing and also in their containers of tin plate. The ratio Pb food/Pb container confirms in some cases that lead of the containers is transfered to food if the value of the ratio is smaller than one. When the ratio is greater than one, food had lead before to put into a container.